KEMUNCULAN ISU RMS DAN PENGARUHNYA DALAM KONFLIK AMBON 1999 - Christian Herman Johan de Fretes (Universitas Kristen Satya Wacana, 2014)
Appearance of Journal Issues RMS (Republik Maluku Selatan) and its influence In Ambon Conflict 1999 aims to explain how the RMS issue emerged and its influence on the conflict that occurred in Ambon. RMS issues never discussed and was never a dominant topic in political and social life in the community of Ambon since in military troops by depleted tumpas TNI in 1962. This lively start RMS issue became a major issue after the 1999 conflict events occur. The conflict which had occurred as a result of the two young men who come from different ethnic groups went on to develop into a conflict between religions. In the midst of the conflict appeared a statement from several parties who claimed that the RMS is the party that is responsible for killing Muslims and sectarian-based State wants to establish Christianity in the South Moluccas. The result of this framing mobilization appeared in large numbers by one religious organization to Ambon will be analyzed using the theory of social movements. The factors of a social movement Framing and mobilization is the process by which allows because of the Political Opportunity (opportunity politics) after the collapse of the authority of Government otoritarian under Suharto. The issue of the RMS developed media by quoting statements from some religious figures and State officials as the responsible party in the conflict. As a result of this issue leads to a wider realm by engaging groups like laskar jihad were sympathetic and moved by emotion because both religious and solidarity as well as nationalism. In addition to the religious solidarity group was also motivated to fight the RMS movement. the prevalence of FKM (Front Kedaulatan Maluku) as the existence of the issue of RMS with its activities later hampered the peace process and will be influential in improving the conflict escalation of Ambon. Keywords: FKM (Front Kedaulatan Maluku), Social Movements, Conflict, Laskar Jihad, RMS